Instruksi Guru EFL dalam Menerapkan MARSI untuk Meningkatkan Strategi Membaca Siswa - Revalina Ulia Agustin Rofieq; Galuh Kirana Dwi Areni (Journal of Education and Teaching Learning, 2026)
Reading comprehension is an essential skill in EFL learning, and students need appropriate reading strategies to support their understanding of texts. However, limited studies have examined how teachers implement metacognitive reading strategies during classroom instruction and how these strategies relate to students’ reading behavior. This study investigated the implementation of MARSI-based reading strategies in an EFL classroom and explored the relationship between teacher instruction and students’ reported reading strategies across the stages of the Genre-Based Approach (GBA). A descriptive qualitative design was employed involving one English teacher and eleventh-grade students in an advanced English class. Data were collected through lesson plan analysis, classroom observation, teacher interviews, and students’ questionnaire adapted from the MARSI framework. The data were analyzed based on the three MARSI categories: Global Reading Strategies (GRS), Problem-Solving Strategies (PSS), and Support Reading Strategies (SRS). The findings revealed that although MARSI-based strategies were not explicitly stated in the lesson plan, the teacher implemented all three categories during classroom instruction. Problem-Solving Strategies and Support Reading Strategies appeared more frequently during reading activities. Students also reported using strategies that were commonly reinforced by the teacher, such as rereading difficult sections, taking notes, identifying important information, and using dictionaries to understand unfamiliar words. These findings indicate that teacher instruction plays an important role in fostering students’ strategic reading behavior and metacognitive awareness in EFL classrooms. The study suggests that integrating metacognitive reading strategies into reading instruction may help students develop more effective and independent reading practices.